Application of Pure Birth to the Phenomenon of Covid-19 Infected Cases in Indonesia with A Time Interval (0, 24) Hours from June to September 2020: Application of Pure Birth to the Phenomenon of Covid-19 Infected Cases in Indonesia with A Time Interval (0, 24) Hours from June to September 2020 - Irmansyah, Athaya Zahrani (Communication In Research And Publications, 2023)
Since the emergence of the 2019 novel coronavirus (2019-nCoV) in Wuhan City, China, in 2019, many countries in the world have been infected with the virus with very serious cases. This has caused a slump, especially for Indonesia, with a lower-middle-class society of 115 million people or 45% of the total population. The virus's rapid spread through droplets resulted in the Indonesian government implementing a lockdown called Large-scale Social Restrictions within months. This system is an effort to break the chain of virus spread. A pure birth process can be called a stochastic process with a continuous parameter space and a discrete state space. This research will focus on the application of the Pure Birth Process, which is expected to provide scientific studies on Covid-19 in Indonesia, become a new reference for the development of mathematics, and provide information on research results so that they can be used in policymaking to overcome and overcome the spread of Covid-19. 19. At the end of this study, it was known that the spread of Covid-19 in Indonesia was very drastic, which had a rate of increase in cases as big as a person/hour or person/day, which is a very significant increase. Based on calculations using Pure Birth, it is hoped that it can be used in policymaking for the government and the community to overcome and overcome the spread of Covid-19.